ANS dez anos depois: percepção dos especialistas em saúde suplementar sobre o eixo de articulação e aprimoramento institucional - Capra, Luciene Pinheiro (2012)
The main objective of this study was to investigate whether the strategic area of improvement and institutional articulation, from the point of view of experts in the health supplement, has evolved over the past ten years. Alternative, also assessed the development of relations with the public interest, transparency in the disclosure of information concerning the sector, improving regulatory capacity, and describe the tools and mechanisms used as a facilitator of the goals mentioned above. Experts consulted indicated progress in all categories studied in this thesis showed important trends and sector regulation. All objectives were achieved and that the end result of the research indicates that in the period delimited, ANS has undergone many changes that have led to its evolution and its mechanisms and tools, offering society a more elaborate setting, refined and despite all the mishaps and need ripening, has been fulfilling the basic assumptions laid out in law and institutions on their axes. The Delphi methodology, used in this study can be used in other strategic areas of the institution, as well as in other case studies. Technically, the tools used to design and administer questionnaires proved to be very effective, and the difficulties of the research did not flee the scene considered common to any academic work. The relevance of this research is the relevant information to the NSA, the public health sector or private, and especially the academia, through the narration of facts and figures new and already known. It is expected that serves as a valuable source of query future researchers.